HUBUNGAN PANJANG TUNGKAI DAN KEKUATAN OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK SISWA KELAS VII SMP NEGERI 4 PEKANBARU - Afdhol Zikri Afdhol Zikri; Ramadi Ramadi '; Ardiah Juita Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract This study was performed using correlation research design that aims to identify some of the correlations between the independent variables and the dependent variable , by looking at the correlation between leg length and leg muscle strength in long jump results squat style . The independent variable is the length of the leg and leg muscle strength , the dependent variable is the result of long jump squat style . The population in this study were male students of class VII SMPN 4 Pekanbaru who enrolled as students in academic year 2013-2014 . Based on preliminary studies of samples taken by 30 male students. This study aims to determine the relationship of leg length and leg muscle strength with the results of the long jump squat style of class VII SMPN 4 Pekanbaru . The hypothesis of this study is that there is a relationship limb length and limb muscle strength with the results of the long jump squat style of male students of class VII SMPN 4 Pekanbaru . The Data collection to carry out tests of leg muscle strength by testing vertical jump and long jump test squat style . The technique of data analysis was performed using statistical analysis of the product moment correlation . Before the data was analyzed, the normalization test was used by using Liliefors Test and regression equation linearity test in advance to do tests with Test Liliefors normalization and at significance level of 0.05. The results of correlation analysis showed an association of leg muscle strength (X) with the results of the long jump squat style of class VII SMPN 4 Pekanbaru. Based on the analysis of data obtained r = 0.892 which is means those by using t test and the results are tcount ttable 4.679 and 1.990 . Means of t > t table . It can be concluded that Ho refused and H1 accepted . It shows a significant correlation between the two variables .Keywords : Limb Muscle Strength , Results Long Jump Squat Style